Electronic and optical properties of novel carbon allotropes. (May 2016) - Wang, Zhanyu; Dong, F.; Shen, B.; Zhang, R.J.; Zheng, Y.X.; Chen, L.Y.; Wang, S.Y.; Wang, C.Z.; Ho, K.M.; Fan, Yuan-Jia; Jin, Bih-Yaw; Su, Wan-Sheng
Abstract: The vibrational properties, electronic structures and optical properties of novel carbon allotropes, such as monolayer penta-graphene (PG), double-layer PG and T12-carbon, were studied by first-principles calculations. Results of phonon calculations demonstrate that these exotic carbon allotropes are dynamically stable. The bulk T12 phase is an indirect-gap semiconductor having a quasiparticle (QP) bandgap of ∼5.19 eV. When the bulk material transforms to a two-dimensional (2D) phase, the monolayer and double-layer PG become quasi-direct gap semiconductors with smaller QP bandgaps of ∼4.48 eV and ∼3.67 eV, respectively. Furthermore, the partial charge density analysis indicates that the 2D phases retain part of the electronic characteristics of the T12 phase. The linear photon energy-dependent dielectric functions and related optical properties including refractive index, extinction coefficient, absorption spectrum, reflectivity, and energy-loss spectrum were also computed and discussed. Additionally, the chemical stability of monolayer PG and the electronic and optical properties of double-side hydrogenated monolayer PG were also investigated. The results obtained from our calculations are beneficial to practical applications of these exotic carbon allotropes in optoelectronics and electronics.